2022
DOI: 10.1002/cmdc.202200495
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Bifunctional Cross‐Bridged Chelating Agent, Peptide Conjugation, and Comparison of 68Ga Labeling and Complex Stability Characteristics with Established Chelators

Abstract: Ga 3 + can be introduced into receptor-specific peptidic carriers via different chelators to obtain radiotracers for Positron Emission Tomography imaging and the chosen chelating agent considerably influences the in vivo pharmacokinetics of the corresponding radiopeptides. A chelator that should be a valuable alternative to established chelating agents for 68 Garadiolabeling of peptides would be a backbone-functionalized variant of the chelator CB-DO2A. Here, the bifunctional crossbridged chelating agent CB-DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Cross‐bridged DOTA, CB‐DO2A, confirmed complete envelopment of the central Ga 3+ ion with more ideal bond distances and bond angles than DOTA 37 . Bifunctional variant of CB‐DO2A, namely, CB‐DO2A‐GA was developed by Damerow et al., and demonstrated a very high kinetic inertness against degradation in human serum of the resulting 68 Ga complex 38 . Using glutaric acid in the CB‐DO2A as conjugation arm enables conjugation to Tyr 3 ‐octreotate (TATE) without alteration of coordination sphere 39,40 …”
Section: Gallium‐68mentioning
confidence: 99%
See 1 more Smart Citation
“…Cross‐bridged DOTA, CB‐DO2A, confirmed complete envelopment of the central Ga 3+ ion with more ideal bond distances and bond angles than DOTA 37 . Bifunctional variant of CB‐DO2A, namely, CB‐DO2A‐GA was developed by Damerow et al., and demonstrated a very high kinetic inertness against degradation in human serum of the resulting 68 Ga complex 38 . Using glutaric acid in the CB‐DO2A as conjugation arm enables conjugation to Tyr 3 ‐octreotate (TATE) without alteration of coordination sphere 39,40 …”
Section: Gallium‐68mentioning
confidence: 99%
“…37 Bifunctional variant of CB-DO2A, namely, CB-DO2A-GA was developed by Damerow et al, and demonstrated a very high kinetic inertness against degradation in human serum of the resulting 68 Ga complex. 38 Using glutaric acid in the CB-DO2A as conjugation arm enables conjugation to Tyr 3 -octreotate (TATE) without alteration of coordination sphere. 39,40 The DOTA derivative, PCTA (3,6,9,15-tetraazabicyclo [9.3.1]pentadeca-1(15),11,13-triene-3,6,9-triacetic acid), originally investigated with lanthanides for use as a potential MRI relaxation agent, is a vast improvement over DOTA for 67/68 Ga-radiotracers.…”
Section: Gallium-68mentioning
confidence: 99%